Naphthalene diimide–amino acid conjugates as novel fluorimetric and CD probes for differentiation between ds-DNA and ds-RNA - Weißenstein, Annike; Vysotsky, Myroslav O.; Piantanida, Ivo; Würthner, Frank (Beilstein Journal of Organic Chemistry, 2020)
Two novel unnatural amino acids, prepared by linking a dicationic purple-coloured and fluorescent naphthalene diimide (NDI) at core position to amino acid side chains of variable length, strongly interacted with ds-DNA/RNA by threading intercalation. Different from a reference NDI dye with identical visible range absorbance (520–540 nm) and Stokes shifts in emission (+60 nm, quantum yield > 0.2), only these amino acid–NDI conjugates showed selective fluorimetric response for GC-DNA in respect to AT(U)-polynucleotides. The DNA/RNA binding-induced circular dichroism (ICD) response of NDI at 450–550 nm strongly depended on the length and rigidity of the linker to the amino acid unit, which controls the orientation of the NDI unit inside within the intercalative binding site. The ICD selectivity also depends on the type of polynucleotide, thus the studied NDI dyes act as dual fluorimetric/ICD probes for sensing the difference between here used GC-DNA, AT-DNA and AU-RNA.
Keywords: amino acid–fluorophore conjugate; circular dichroism; DNA/RNA recognition; fluorescence; intercalation; naphthalene diimide

(untitled) - Matić, J.; Tumir, L.-M.; Radić Stojković, M.; Piantanida, I. (Curr. Protein Pept. Sci., 2016)

Supermolecular Dye Chemistry - Ihmels, H.; Otto, D. (Intercalation of organic dye molecules into double-stranded DNA - general principles and recent developments, 2005)

(untitled) - Dervan, P. B.; Edelson, B. S. (Curr. Opin. Struct. Biol., 2003)

(untitled) - Müller, S.; Paulus, J.; Mattay, J.; Ihmels, H.; Dodero, V. I.; Sewald, N. (Beilstein J. Org. Chem., 2020)

(untitled) - Bhaduri, S.; Ranjan, N.; Arya, D. P. (Beilstein J. Org. Chem., 2018)

(untitled) - Kaur, G.; Lewis, J. S.; van Oijen, A. M. (Molecules, 2019)

(untitled) - Specht, E. A.; Braselmann, E.; Palmer, A. E. (Annu. Rev. Physiol., 2017)

Small Molecule DNA and RNA Binders: From Synthesis to Nucleic Acid Complexes - Demeunynck, M.; Bailly, C.; Wilson, W. D. (Wiley-VCH, 2004)

(untitled) - Lavis, L. D. (Biochemistry, 2017)

(untitled) - Teo, Y. N.; Kool, E. T. (Chem. Rev., 2012)

(untitled) - Šmidlehner, T.; Rožman, A.; Piantanida, I. (Curr. Protein Pept. Sci., 2019)

(untitled) - Matić, J.; Šupljika, F.; Tandarić, T.; Dukši, M.; Piotrowski, P.; Vianello, R.; Brozović, A.; Piantanida, I.; Schmuck, C.; Radić Stojković, M. (Int. J. Biol. Macromol., 2019)

(untitled) - Šmidlehner, T.; Kurutos, A.; Slade, J.; Belužić, R.; Ang, D. L.; Rodger, A.; Piantanida, I. (Eur. J. Org. Chem., 2018)

(untitled) - Šmidlehner, T.; Badovinac, M.; Piantanida, I. (New J. Chem., 2018)

(untitled) - Maity, D.; Matković, M.; Li, S.; Ehlers, M.; Wu, J.; Piantanida, I.; Schmuck, C. (Chem. – Eur. J., 2017)

(untitled) - Wu, J.; Zou, Y.; Li, C.; Sicking, W.; Piantanida, I.; Yi, T.; Schmuck, C. (J. Am. Chem. Soc., 2012)

(untitled) - Suraru, S.-L.; Würthner, F. (Angew. Chem., Int. Ed., 2014)

(untitled) - Al Kobaisi, M.; Bhosale, S. V.; Latham, K.; Raynor, A. M.; Bhosale, S. V. (Chem. Rev., 2016)

(untitled) - Maniam, S.; Higginbotham, H. F.; Bell, T. D. M.; Langford, S. J. (Chem. – Eur. J., 2019)

(untitled) - Cox, R. P.; Sandanayake, S.; Scarborough, D. L. A.; Izgorodina, E. I.; Langford, S. J.; Bell, T. D. M. (New J. Chem., 2019)

(untitled) - Czerwinska, I.; Sato, S.; Juskowiak, B.; Takenaka, S. (Bioorg. Med. Chem., 2014)

(untitled) - Rhoden Smith, A.; Iverson, B. L. (J. Am. Chem. Soc., 2013)

(untitled) - Würthner, F.; Ahmed, S.; Thalacker, C.; Debaerdemaeker, T. (Chem. – Eur. J., 2002)

(untitled) - Kim, M. B.; Dixon, D. W. (J. Phys. Org. Chem., 2008)

(untitled) - Thalacker, C.; Röger, C.; Würthner, F. (J. Org. Chem., 2006)

(untitled) - Saftić, D.; Radić Stojković, M.; Žinić, B.; Glavaš-Obrovac, L.; Jukić, M.; Piantanida, I.; Tumir, L.-M. (New J. Chem., 2017)

(untitled) - Radić Stojković, M.; Piotrowski, P.; Schmuck, C.; Piantanida, I. (Org. Biomol. Chem., 2015)

(untitled) - Schäfer, K.; Ihmels, H.; Porcù, E.; Viola, G. (Chem. – Eur. J., 2017)

(untitled) - Wong, P.; Lee, C.; Tannock, I. F. (Clin. Cancer Res., 2005)

(untitled) - Manallack, D. T.; Prankerd, R. J.; Yuriev, E.; Oprea, T. I.; Chalmers, D. K. (Chem. Soc. Rev., 2013)

(untitled) - Weißenstein, A.; Grande, V.; Saha-Möller, C. R.; Würthner, F. (Org. Chem. Front., 2018)

Gaussian 09 (Gaussian, Inc., 2009)

(untitled) - Sakai, N.; Mareda, J.; Vauthey, E.; Matile, S. (Chem. Commun., 2010)

(untitled) - Pugliesi, I.; Megerle, U.; Suraru, S.-L.; Würthner, F.; Riedle, E.; Lochbrunner, S. (Chem. Phys. Lett., 2011)

(untitled) - Casagrande, V.; Alvino, A.; Bianco, A.; Ortaggi, G.; Franceschin, M. (J. Mass Spectrom., 2009)

Biophysical Chemistry - Cantor, C. R.; Schimmel, P. R. (WH Freeman and Co., 1980)

Principles of Nucleic Acid Structure - Egli, M.; Saenger, W. (Springer, 1983)

(untitled) - Hewitt, W. M.; Calabrese, D. R.; Schneekloth, J. S., Jr (Bioorg. Med. Chem., 2019)

(untitled) - Mergny, J.-L.; Lacroix, L. (Oligonucleotides, 2003)

(untitled) - Scatchard, G. (Ann. N. Y. Acad. Sci., 1949)

(untitled) - McGhee, J. D.; von Hippel, P. H. (J. Mol. Biol., 1974)

(untitled) - McGhee, J. D.; von Hippel, P. H. (J. Mol. Biol., 1976)

(untitled) - Piantanida, I.; Palm, B. S.; Žinić, M.; Schneider, H.-J. (J. Chem. Soc., Perkin Trans. 2, 2001)

(untitled) - Chaires, J. B. (Arch. Biochem. Biophys., 2006)

(untitled) - Breslauer, K. J.; Remeta, D. P.; Chou, W. Y.; Ferrante, R.; Curry, J.; Zaunczkowski, D.; Snyder, J. G.; Marky, L. A. (Proc. Natl. Acad. Sci. U. S. A., 1987)

Methods in Cell Biology - Freyer, M. W.; Lewis, E. A. (Isothermal titration calorimetry: experimental design, data analysis, and probing macromolecule/ligand binding and kinetic interactions, 2008)

Biocalorimetry: Applications of Calorimetry in the Biological Sciences - Ladbury, J. E.; Chowdhry, B. Z. (John Wiley & Sons, Inc., 1998)

Methods in Enzymology - Eriksson, M.; Nordén, B. (Linear and circular dichroism of drug-nucleic acid complexes, 2001)

(untitled) - Šmidlehner, T.; Piantanida, I.; Pescitelli, G. (Beilstein J. Org. Chem., 2018)

(untitled) - Murr, M. M.; Harting, M. T.; Guelev, V.; Ren, J.; Chaires, J. B.; Iverson, B. L. (Bioorg. Med. Chem., 2001)

(untitled) - Strekowski, L.; Wilson, B. (Mutat. Res., Fundam. Mol. Mech. Mutagen., 2007)

(untitled) - Lee, J.; Guelev, V.; Sorey, S.; Hoffman, D. W.; Iverson, B. L. (J. Am. Chem. Soc., 2004)

(untitled) - Smith, C. K.; Brannigan, J. A.; Moore, M. H. (J. Mol. Biol., 1996)

(untitled) - Zou, T.; Sato, S.; Yasukawa, R.; Takeuchi, R.; Ozaki, S.; Fujii, S.; Takenaka, S. (Molecules, 2020)

(untitled) - Sato, S.; Kajima, A.; Hamanaka, H.; Takenaka, S. (J. Organomet. Chem., 2019)

(untitled) - Kaneyoshi, S.; Zou, T.; Ozaki, S.; Takeuchi, R.; Udou, A.; Nakahara, T.; Fujimoto, K.; Fujii, S.; Sato, S.; Takenaka, S. (Chem. – Eur. J., 2020)

(untitled) - Ban, Ž.; Matić, J.; Žinić, B.; Foller Fuchtbauer, A.; Wilhelmsson, L. M.; Piantanida, I. (Molecules, 2020)

Principles of Fluorescence Spectroscopy - Lakowitz, J. R. (Kluwer Acacemic Publishers, 1999)

(untitled) - Chaires, J. B.; Dattagupta, N.; Crothers, D. M. (Biochemistry, 1982)

(untitled) - Tumir, L.-M.; Piantanida, I.; Juranović Cindrić, I.; Hrenar, T.; Meić, Z.; Žinić, M. (J. Phys. Org. Chem., 2003)

(untitled) - Klemm, K.; Radić Stojković, M.; Horvat, G.; Tomišić, V.; Piantanida, I.; Schmuck, C. (Chem. – Eur. J., 2012)